Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3389/fnhum.2016.00581
|View full text |Cite
|
Sign up to set email alerts
|

Neural Mechanisms of Positive Mood Induced Modulation of Reality Monitoring

Abstract: This study investigates the neural mechanisms of mood induced modulation of cognition, specifically, on reality monitoring abilities. Reality monitoring is the ability to accurately distinguish the source of self-generated information from externally-presented contextual information. When participants were in a positive mood, compared to a neutral mood, they significantly improved their source memory identification abilities, particularly for self-generated information. However, being in a negative mood had no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 55 publications
(81 reference statements)
3
30
0
2
Order By: Relevance
“…Prior research has revealed that both positive mood states and positive rewarding stimuli enhance preparatory activity within the mPFC to facilitate subsequent cognitive performance (Subramaniam et al, 2009; Subramaniam, Faust, et al, 2012; 2016), and that the mPFC supports reality monitoring task performance (better identification of self-generated items) in HC participants (Subramaniam, Luks, et al, 2012; 2016). In our previous fMRI study examining positive mood–cognition interactions, (Subramaniam et al, 2009), the PCC also showed increased activity during a preparation period preceding problem-solving, and was a positive mood-sensitive region that facilitated subsequent problem-solving in HC participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research has revealed that both positive mood states and positive rewarding stimuli enhance preparatory activity within the mPFC to facilitate subsequent cognitive performance (Subramaniam et al, 2009; Subramaniam, Faust, et al, 2012; 2016), and that the mPFC supports reality monitoring task performance (better identification of self-generated items) in HC participants (Subramaniam, Luks, et al, 2012; 2016). In our previous fMRI study examining positive mood–cognition interactions, (Subramaniam et al, 2009), the PCC also showed increased activity during a preparation period preceding problem-solving, and was a positive mood-sensitive region that facilitated subsequent problem-solving in HC participants.…”
Section: Discussionmentioning
confidence: 99%
“…The mPFC/ACC is also a region that is also modulated by positive mood states and positive rewarding stimuli in Healthy Control (HC) participants to facilitate cognitive outcomes (Knutson & Cooper, 2005; Subramaniam, Kounios, Parrish, & Jung-Beeman, 2009; Subramaniam, Faust, Beeman, & Mashal, 2012; 2016). In our previous functional Magnetic Resonance Imaging (fMRI) studies of mood–cognition interactions in HC participants, we found two additional regions within posterior cingulate cortex (PCC) and putamen that showed positive mood-sensitive signals, which also modulated upcoming cognitive performance (Subramaniam et al, 2009; Subramaniam & Vinogradov, 2013; 2016). In general, we expected a positive mood state to modulate a network of regions in HC participants, including prefrontal cortices, PCC, parahippocampal cortices, and basal ganglia, consistent with previous research which has shown recruitment of these regions during positive mood states, and during overall episodic source memory retrieval (Elward et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…We and others have also demonstrated that the mPFC plays a critical function in mediating interactions between mood and higher-order cognition during reality-monitoring (7,12). These prior correlative imaging studies which show that mPFC supports both reality monitoring and mood enhancement underscore the critical need to investigate whether mPFC can causally impact reality monitoring decision-making and mood.…”
Section: Significance Statementmentioning
confidence: 53%
“…We have previously demonstrated in our fMRI studies that mPFC activation correlates with improved reality monitoring not only in HC, but also in psychiatric patient populations (i.e., patients with mood and psychotic disorders such as schizophrenia and schizoaffective disorders) (3,7,12). Psychosis typically emerges during excessive pruning of excitatory pathways, leading to hypoactive aberrant networks in the PFC (21,22).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation